‘Time’ in tourism: ‘individual time’ and ‘social time’ - Bonneau, Michel (Turyzm/Tourism, 2009)
The author does a review of the research into tourist activity and concludes that the particular character of tourist behaviour is reflected best in the study of time budgets. He proposes Max Weber's ideal-type method to be used in the analysis. In the conclusions to the article the author presents typical examples of qualitative time (recreation, holidays, tourism).